Arcus Divi Constantini: An Architectural Analysis and Chronological Proposal for the Arch of Janus in the Forum Boarium in Rome. (10th April 2017) - Mateos, Pedro; Pizzo, Antonio; Ventura, Ángel
Abstract: In this article we present a new study of the Arch of Janus, analysing previously unpublished aspects of its architecture and chronology based on new data obtained from a recent research project. This study provides the first complete planimetric view of the monument, together with a stratigraphic reading of the structure, evaluating the different elements of spolia that were re-used in its construction. Also, the discovery of a new inscription that was re-used in building the arch finally confirms that it dates from the period of Constantius II (a.d . 357). Finally, we present a proposal for the reconstruction of the dedicatory inscription of the arch, preserved in the nearby church of San Giorgio al Velabro.